Synthesis and Characterization of Ni(II) Schiff Base Complex as a Precursor for NiO Nanoparticles and an Investigation of Their Corrosion Inhibition - Raji, Shahad Qasim; Bader, Ali Talib (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
This study first aimed to synthesize and characterize a [Ni(C14H13NO2)(OAC)2(H2O)2] via the preparation of a ligand, coordination with Ni(II) ions, and full characterization, such as